Findings of diabetic macular edema on OCT and its correlation with visual acuity - M. Nirmala; Kola Vijaya Sekhar; G. S. Ramesh Kumar; P.D.S.Keerthi; D.Srilakshmi (International Journal of Health and Clinical Research, 2021)
Aim: to describe various findings of Diabetic Macular Edema (DME) demonstrated by Optical Coherence Tomography (OCT) and correlate them with Visual Acuity. Methods and materials: sample of 50 patients with diabetic retinopathy detected to have clinically significant macular edema, and macular thickening with Optical coherence tomography are included in the study. Results: A statistically significant difference was found with P Value <0.05 , indicating that morphological subtypes/patterns of DME on OCT varied with the severity of retinopathy .The preponderance of Diabetic Macular Edema is more in the age group of 51-60 years (54%) and in patients with a history of DM for 6-10 years(48%). Conclusion: The mean Central Subfield Thickness varied among Various patterns of DME on OCT. Highest mean CST was observed in SRD pattern (497.15μm), and Least mean CST was observed in DRT pattern (332.69μm). Visual acuity varied among various patterns of DME on OCT. Worst mean Visual Acuity was observed in SRD pattern 1.6 log MAR(Snellen equivalent-6/250)and best mean visual acuity was observed in DRT pattern 0.6 log MAR(Snellen equivalent-6/24).